The comparison of sex differences in depression-like behaviors and neuroinflammatory changes in a rat model of depression induced by chronic stress - Xia, Juan; Wang, Haoyin; Zhang, Cai; Liu, Baiping; Li, Yuyu; Li, Kangwei; Li, Peng; Song, Cai (Frontiers in Behavioral Neuroscience, 2023)
Background: Clinical prevalence of major depression is higher in women than men, while the psychoneuroimmunological mechanisms underlying the differences between two sexes are not fully understood. Methods: The present study explored sex differences in the behaviors and depressive pathological mechanisms induced by chronic unpredictable mild stress (CUMS). Depression- and anxiety-like behaviors were assessed by the sucrose preference test (SPT), force swimming test (FST), open field test (OFT) and elevated plus-maze (EPM). The enzyme-linked immunosorbent assay (ELISA) was used to measure cytokine concentrations, high-performance liquid chromatography (HPLC) was used to measure for monoamine neurotransmitters and metabolite contents, and real-time quantitative PCR (qPCR) and western blotting (WB) were used to measure glial parameters in the hippocampus. Results: Under control conditions, female rats exhibited shorter immobility times in the FST, lower interferon-γ and interleukin (IL)-4 levels in the hippocampus, lower norepinephrine (NE) and homovanillic acid (HVA), and higher p75 and glial-derived neurotrophic factor (GDNF) expression than male rats. CUMS markedly reduced rat body weight gain, sucrose preference, locomotor activity, number of entries into the central zone and rearing in the OFT, as well as the number of entries into and time spent in open arms of the EPM; however, CUMS increased the immobility times of the rats of both sexes in the FST. Interestingly, more pronounced changes in sucrose preference and locomotor activity were observed in female rats than in males. Consistently, CUMS-increased glucocorticoid concentration, M1 microglial marker CD11b, and peripheral IL-1β and IL-4, while decreased hippocampal IL-10, serotonin (5-HT), dopamine metabolite 3,4-dihydroxyphenylacetic acid (DOPAC) and norepinephrine metabolite 3-methoxy-4-hydroxyphenylglycol (MHPG) were more significant in females than males. Conclusion: These data revealed possible mechanisms by which females suffer more depression than males at least in stressful environment.